Moderenisasi & Demokratisasi Pendidikan Islam : Kajian Konstruktif Lembaga Perguruan Tinggi Islam di Indonesia - Rofiqi, Rofiqi; Fuad, Ah. Zakki; Bakar, M. Yunus Abu (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
Islamic Education must engage in dialogue with the dynamics of social life and technological developments. Through the modernization and democratization of Islamic Education, Azyumardi Azra offers an educational construction that can face the challenges of modernity by adhering to the values and teachings of the Islamic religion. This research aims to reveal Azyumardi Azra's views and conception of Islamic Education and their implications for the construction of Islamic Education. This study uses a qualitative approach with the type of library research. The results of this study indicate that Islamic Education in Azra's view, must be oriented towards the formation and development of children's personality based on the teachings of Islam. Not only that, Islamic Education must also be designed considering students' competence in mastering science and technology. In this way, it can carry out its function of preparing human resources thoroughly. To modernize and democratize Education, Azra offers several strategic steps, including; ideological-normative, political, economic, social, and cultural mobilization. At the same time, Azra also uncovered several variables that must become a modernization agenda: administrative modernization, subcultural modernization, and capacity expansion. In addition, according to Azra, efforts to democratize Education are more to make the education system more just, inclusive, and participatory. According to him, the democratization of Education is a process of social change that aims to make the education system more equitable and of better quality for all citizens. He believes that democratization in Education can be characterized by three key aspects. Firstly, it involves having a flexible curriculum that allows students to express their creativity. Secondly, there is a shift in the paradigm of Islamic Education, moving away from an authoritarian approach towards a more democratic one. Lastly, there is a harmonious connection between Islamic educational institutions and the surrounding community, ensuring a synchronized and inclusive learning environment